Subcutaneous ICD and ventricular tachycardia degeneration. Issue 3 (2017) - Mengoni, Anna; Carluccio, Erberto; Zingarini, Gianluca; Ambrosio, Giuseppe; Tordini, Alessandra; Biagioli, Paolo; Giannandrea, David; Cavallini, Claudio
No abstract available